Preliminary Survey Results From a Medieval Islamic Settlement Site in Eastern Ethiopia: First Archaeological Insight from Fedis - Siraj, Endris Hussien; Abubaker, Meftuh S.; Mohammed, Habir (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2024)
Islam in Ethiopia has a profound impact as one of the streams of its long history. It has been present in the country for almost one and a half millennia. It was first introduced to Axum in northern Ethiopia in AD 615, also referred to as the ‘first hijra’, followed by the subsequent expansions to Shoa in central and eastern Ethiopia through Dahlak and Zeila ports since the 9th century AD. The main agents of these expansions were caravan traders and refugees. Coinciding with such intensified trade and the Islamisation process, eastern Africa witnessed the emergence and consolidation of several Muslim principalities, including in modern-day Ethiopia, from the 11th century AD onwards. Fedis, as one of those principalities within modern-day Ethiopia, was mentioned in Amde Seyon’s chronicle in the 14th century AD. However, Islamic history and archaeology in Ethiopia remain understudied until recently. As part of this negligence, Fedis site has never been studied until the completion of this research. Inspired by its historical mentions and an old map revealing several ruins of settlement sites south of Harar, the researchers conducted a preliminary survey of this particular site in 2021 and 2022. Accordingly, various remains were identified from Fedis that confirmed the site’s archaeological potential. During the fieldwork, ruins of an elaborate stone-built defensive wall, a succession of mosques, a stepwell, carnelian-made seal carved with Arabic text, beads of various kinds, storage pits of different sizes and burials were the findings explored, among many others. As confirmed from these findings, this pilot research sheds new and first archaeological insight into the medieval Islamic site of Fedis in eastern Ethiopia.